Analisis Dampak Covid-19 Terhadap Perubahan Perilaku Konsumen Hypermart - Yudha, Eka Purna; Nurrahman, Iqbal; Modjo, Andhika Rangga Kusuma; Benyamin, Gamaliel (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The Covid-19 pandemic has put pressure on various sectors in the world, including in Indonesia. Since the entry of the COVID-19 virus into Indonesia in March 2020, the government's efforts to prevent the spread of COVID-19 have been Large-Scale Social Restrictions (PSBB) which have had a significant impact on the Indonesian economy on the retail business in Indonesia. This study aims to see if there has been a change in Hypermart consumer behavior before and after the covid-19 pandemic, ranging from spending, shopping frequency, shopping time, to the vehicle used by using a research design in the form of a descriptive research design that uses a quantitative approach. Changes in Hypermart consumer behavior before and after covid-19, especially in average spending and shopping frequency. Where the average expenditure and frequency of shopping for Hypermart consumers after the pandemic tends to decrease when compared to before the covid-19 pandemic.